Robust Control System for Missiles in the Presence of Uncertainty and Disturbances: A Comprehensive Review - Nasiya N.; Amal A. (International Journal of Satellite Remote Sensing, 2024)
In today's warfare and defense systems, when precise and quick maneuvering is essential for mission accomplishment, missiles play a critical role. Nonetheless, the intricacy of missile dynamics by itself, combined with external disruptions and unpredictabilities in operational circumstances, provides challenging but ambitious conditions for achieving precise trajectory tracking and robust flight control. Missiles perform in highly dynamic and uncertain environments where factors such as aerodynamic disturbances, various atmospheric conditions, and sensor inaccuracies can drastically impact their trajectory and effectiveness. Robust control systems are designed to mitigate those demanding situations by means of incorporating techniques that can adapt to uncertainties and disturbances in real-time, ensuring stable and precise control all through the flight trajectory. Without robust control mechanisms, missiles may exhibit poor tracking accuracy, reduced stability, and compromised reliability, leading to diminished mission success rates and increased susceptibility to interception or countermeasures. In this paper various robust control approaches have been explored, including nonlinear disturbance observer-based control, hybrid control strategies, extended state observer-based control, backstepping control, and finite-time control methods. Each approach is analyzed in terms of its theoretical foundations, implementation details, benefits, obstacles and also discusses the realistic implications and capacity applications of these robust manipulate structures in enhancing the overall performance and reliability of missile steerage and manage system.
Keywords: Autopilot; backstepping control; ballistic missile; disturbance observer; extended state observer